VIDEO TUTORIAL SEBAGAI SUPELMEN MEDIA PELATIHAN PIANO BERBASIS DIGITAL UNTUK PEMULA DEWASA - Annisa, Auliya Ayu; Karyono, Tri (Jurnal Penelitian Musik, 2021)
This research is based on the condition of adult beginners who study piano in a course institution but are constrained by internet network disturbances. Thus the researchers created a digital-based piano training concept by adding video tutorials as a supplement to piano training media. Video tutorials are online instructional videos that are connected indirectly with content in the form of stages to carry out specific activities. The use of this video tutorial is intended for beginner piano students aged 9 years or older who are then categorized as adult beginners. The author made this article using the interview method and literature review. The results of this study are 5 piano teachers using video conferencing technology on the zoom application for the concept of digital-based piano training; The advantage of digital-based piano training is that both piano teachers and adult beginners can learn piano anytime and anywhere; while the weakness of digital-based piano training is the internet network which is sometimes disconnected and delayed; On this concept, tutorial videos are shared via whatsapp app before piano training meeting on zoom app; There are 5 stages in making video tutorials, namely 1) Planning materials and indicators of competency achievement; 2) Finding ideas and imagining the concept; 3) Creating Story Lines; 4) Making PPT, writing melody scripts and recording audio visuals; 5) Editing